Venous-arterial CO2 difference in children with sepsis and its correlation with myocardial dysfunction (2019)
Objective: This study aimed to determine the association between venous-arterial CO2 difference (Pv-aCO2) and clinical outcomes of interest in children with severe sepsis and septic shock. Design: An analytical observational study of a prospective cohort was conducted. Setting: The study was carried out from January 2015 to January 2018 in the pediatric intensive care unit of a referral hospital. Materials and methods: Of a total of 1159 patients who were admitted to pediatric critical care, 375 had severe sepsis and septic shock, of which 67 fulfilled the inclusion criteria. Arterial and venous gases were drawn simultaneously with a transthoracic echocardiogram, Pv-aCO2, and other measures of tissue perfusion such as arterial lactate, venous, and evolution to multiple organ failure. Measurements and main results: Half (53.7%) of the patients were under 24 months old, with a slight predominance of male patients. The main site of infection was the lungs in 56% of the cases, with a 91.2% survival rate. Patients who died had a higher venous lactate level (interquartile range 16.2-33.6, p = 0.02). However, there was no correlation between myocardial dysfunction seen on echocardiogram and a Pv-aCO2 greater than 6 mm Hg in children with severe sepsis and septic shock (r = 0.13). Pv-aCO2 and central venous saturation had low sensitivity to detect multiple organ failure and poor correlation with the number of compromised systems (r = 0.8). Conclusion: Pv-aCO2 was not associated with myocardial dysfunction, measured by echocardiogram, in children with severe sepsis and septic shock. It also did not correlate with the number of organs involved or mortality. © 2019 Fernández-Sarmiento, Carcillo, Eraso-Díaz del Castillo, Barrera, Orozco, Rodríguez, Gualdrón, licensee HBKU Press.